# If <span lang="EN

Given,

P(x) = …(1)

P(y) =

P(x).P(y) =

P(x).P(y) =

We know that-

cos x cos y + sin x sin y = cos (x – y)

cos x sin y + sin x cos y = sin (x + y)

and cos x cos y – sin x sin y = cos (x + y)

P(x).P(y) =

In comparison with equation 1 we can say that:

…(2)

P(x).P(y) = P(x + y)

Similarly, we can show for P(y).P(x):

P(y).P(x) =

By matrix multiplication, we have –

P(y).P(x) =

P(y).P(x) =

P(y).P(x) = …(3)

From equation 2 and 3:

P(x).P(y) = P(y).P(x) = P(x + y) …ans

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers